2001
DOI: 10.1002/etc.5620200626
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of a photooxidized polycyclic aromatic hydrocarbon and copper on photosynthesis and plant growth: Evidence that in vivo formation of reactive oxygen species is a mechanism of copper toxicity

Abstract: Heavy metals and polycyclic aromatic hydrocarbons (PAHs) are often cocontaminants in industrialized environments, yet little is known about either the extent or mechanisms of their cotoxicity. To address this shortfall, the combined effects of an oxygenated PAH, 1,2-dihydroxyanthraquinone (1,2-dhATQ), and a heavy metal, Cu2+, on photosynthesis and growth of the duckweed (Lemna gibba) were evaluated. Using assays of chlorophyll a fluorescence and photosystem I activity, 1,2-dhATQ inhibited electron transport at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 51 publications
1
76
0
Order By: Relevance
“…Response addition and concentration addition were relatively rare. These observations suggest that, at least in binary tests, nonadditive interactions between a variety of metals and PAH occur frequently in benthic copepods and perhaps other aquatic plants [31] and animals [32] and that the combination of Cd and PAH may be especially toxic.…”
Section: Discussionmentioning
confidence: 96%
“…Response addition and concentration addition were relatively rare. These observations suggest that, at least in binary tests, nonadditive interactions between a variety of metals and PAH occur frequently in benthic copepods and perhaps other aquatic plants [31] and animals [32] and that the combination of Cd and PAH may be especially toxic.…”
Section: Discussionmentioning
confidence: 96%
“…Based on these, the photosynthesis of B. juncea was more sensitive to low applied Cu concentration, while B. napus showed susceptibility to more serious excess Cu (25 and 50 µM Cu). Considering the remarkable ROS accumulation detected in the leaves we can assume that chloroplast membranes may suffer Cu-induced peroxidation, which can partially explain the diminution of photosynthetic efficiency [3]. Furthermore, free radicals can damage the photosynthetic apparatus [2] and may also catalyse protein degradation through oxidative modification and increased proteolytic activity [38], which may also lead to the decrease in photosynthesis.…”
Section: Pigment Composition and Photosynthetic Capacitymentioning
confidence: 99%
“…Therefore, it is suggested that that concentrations of CMQ C 5 mg L -1 cause PSII inactivity and linear electron flow blockage in M. aeruginosa, leading to the formation of oxygen radicals and consequent oxidative stress. (Babu et al 2001;Nishiyama et al 2006). A conserved gene in eukaryotes and prokaryoters, prx, encodes the Prx protein that plays an important role in catalyzing the reduction of oxygen radicals, such as H 2 O 2 , alkyl hydroperoxides, and peroxynitrite (Wood et al 2003).…”
Section: Resultsmentioning
confidence: 99%